Systemic Organ Wasting Induced by Localized Expression of the Secreted Insulin/IGF Antagonist ImpL2. - Kwon, Y.; Song, W.; Droujinine, I.A.; Hu, Y.; Asara, J.M.; Perrimon, N. (Developmental Cell, 2015)
Organ wasting, related to changes in nutrition and metabolic activity of cells and tissues, is observed under conditions of starvation and in the context of diseases, including cancers. We have developed a model for organ wasting in adult Drosophila, whereby overproliferation induced by activation of Yorkie, the Yap1 oncogene ortholog, in intestinal stem cells leads to wasting of the ovary, fat body, and muscle. These organ-wasting phenotypes are associated with a reduction in systemic insulin/IGF signaling due to increased expression of the secreted insulin/IGF antagonist ImpL2 from the overproliferating gut. Strikingly, expression of rate-limiting glycolytic enzymes and central components of the insulin/IGF pathway is upregulated with activation of Yorkie in the gut, which may provide a mechanism for this overproliferating tissue to evade the effect of ImpL2. Altogether, our study provides insights into the mechanisms underlying organ-wasting phenotypes in Drosophila and how overproliferating tissues adapt to global changes in metabolism.